Mozambique Rising : Building a New Tomorrow - Ross, Doris (Departmental Papers; Departmental Paper ;, 2014)
The countries in the East African Community (EAC) are among the fastest-growing economies in sub-Saharan Africa. This report highlights Mozambique's remarkably strong growth over the two decades since the end of the civil war in 1992, as well as the major challenges that remain for the country to rise out of poverty and further its economic development.